2021
DOI: 10.7705/biomedica.5598
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis y rickettsiosis, reto diagnóstico para el síndrome febril en zonas endémicas

Abstract: Se presenta el caso de un hombre de 50 años de edad proveniente de la región de Urabá, Colombia, con una infección mixta por Rickettsia rickettsii y Leptospira interrogans serovar Copenhageni ST78, y pruebas negativas para malaria y dengue.El paciente presentó un síndrome febril que no mejoró con el tratamiento antibiótico sistémico y, finalmente, falleció en la unidad de cuidados intensivos. El diagnóstico post mortem se hizo mediante tipificación molecular de los dos agentes etiológicos. En la inspección del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The concomitant seroprevalent and seroincident findings provide evidence of individuals in Urabá, Colombia, who have been exposed to both microorganisms without developing overt clinical disease or being diagnosed. Our result carries important public health implications, as clinical case reports have indicated that individuals susceptible to concurrent infections by rickettsioses and leptospirosis may experience more severe clinical manifestations and potentially fatal outcomes( 18 , 22 ).…”
Section: Discussionmentioning
confidence: 80%
“…The concomitant seroprevalent and seroincident findings provide evidence of individuals in Urabá, Colombia, who have been exposed to both microorganisms without developing overt clinical disease or being diagnosed. Our result carries important public health implications, as clinical case reports have indicated that individuals susceptible to concurrent infections by rickettsioses and leptospirosis may experience more severe clinical manifestations and potentially fatal outcomes( 18 , 22 ).…”
Section: Discussionmentioning
confidence: 80%
“…Cardona-Ospina et al ., presented cases indicating that concurrent viral co-infections with leptospirosis might have contributed to fatal outcomes [ 68 ]. Similarly, Ramírez-García R et al [ 67 ] reported a case of concurrent leptospirosis and rickettsiosis infection in a patient with a high-risk occupational history in an endemic area for tropical diseases. The patient exhibited progressive and ultimately fatal clinical symptoms [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ramírez-García R et al [ 67 ] reported a case of concurrent leptospirosis and rickettsiosis infection in a patient with a high-risk occupational history in an endemic area for tropical diseases. The patient exhibited progressive and ultimately fatal clinical symptoms [ 67 ]. Consequently, leptospirosis should be considered as a potential cause of the febrile syndrome, not only as an isolated agent but also as a possible co-infection that can have serious implications for patient health and may be associated with increased mortality rates [ 30 , 65 , 67 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, tropical infectious diseases lead to melancholy of more than one billion people’s lives with one-half of deaths annually. Children are more prone to tropical infections and every year, one-third of the infected children die due to malaria [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%